The Readability Study: A Randomised Trial of Health Information Written at Different Grade Reading Levels - Mac, Olivia; Ayre, Julie; McCaffery, Kirsten; Boroumand, Farzaneh; Bell, Katy; Muscat, Danielle M. (Journal of general internal medicine : JGIM, 2025)
Despite increasing attention on health literacy and the inclusion of grade reading level recommendations in guidelines, it remains unclear if lowering the grade reading level of written health information to specific target grades improves patient-related outcomes. To assess whether grade reading level of written information affects knowledge, perceived reading ease, acceptability and trustworthiness of information and, to explore whether information written at a lower grade reading level reduces disparities in outcomes across health literacy levels. We conducted a 4-arm online randomized trial with a community sample of adults living in Australia from 31 July to 20 September 2023. Participants were randomised to one of four arms: Information about sciatica and knee osteoarthritis written at a grade 8, 10, 12 or 14 reading level. Readability was assessed using the SMOG Index and iteratively revised to each lower grade. Primary outcome was knowledge of health conditions. Secondary outcomes were brief knowledge, perceived reading ease, acceptability (i.e., perceived usefulness and likelihood to recommend) and trustworthiness of information. 2235 participants were randomised and included in the analysis. Mean age was 41 years and 54.5% identified as female. Low health literacy was identified in 28.2% of participants. We found no evidence of a main effect of grade reading level on knowledge (grade 8: 9.0 (SD = 2.7), grade 10: 9.1 (SD = 2.6), grade 12: 8.9, grade 14: 9.1 (SD = 2.7). Participants with high health literacy had higher knowledge scores overall, however, there was no evidence that health literacy modified the effect of grade reading level. There were no significant differences in any of the secondary outcomes. Our study showed no difference in knowledge when grade reading level was manipulated alone. Our findings indicate there is limited value in reducing grade reading level without attention to other health literacy principles. ACTRN12623000224628p.